The Influence of Job and Individual Resources on Work Engagement Among Chinese Police Officers: A Moderated Mediation Model - Lan, Ting; Chen, Meirong; Zeng, Xiaoqing; Liu, Ting (Frontiers in Psychology, 2020)
Background: The work engagement of police officers pertains to social stability and security, as well as to the orderly operation of the political-economic environment. Although there are many studies on work engagement at present, few studies focus on the influencing factors of police officers’ work engagement. According to the job demands-resources model and the conservation of resources theory, organizational job resources (e.g., perceived organizational support) and personal resources (e.g., regulatory emotional self-efficacy) are important factors influencing work engagement. We assume a moderated mediation model in which job satisfaction plays a mediating role in the relationship between perceived organizational support and work engagement, regulatory emotional self-efficacy moderates not only the relationship between perceived organizational support and job satisfaction but also the relationship between job satisfaction and work engagement. Objective and Method: This study explores the drivers of work engagement through perceived organizational support and regulatory emotional self-efficacy among Chinese police officers using a convenient sampling method to administer a questionnaire to 744 Chinese police officers. A mediated model is proposed to investigate the mediating role of job satisfaction and the regulating role of regulatory emotional self-efficacy. Results: Job satisfaction mediated a positive relationship between organizational support and work engagement, and the perceived organizational support-job satisfaction and the job satisfaction-work engagement relationships were positively moderated by regulatory emotional self-efficacy, such that these relationships were stronger at higher levels of regulatory emotional self-efficacy. These findings, have a practical significance for Chinese police officers’ work engagement advancement.